Ginger Tea on Dysmenorrhoea Among Nursing Students - Crasta, Sheetal; Fernandes, Philomena; Paul, Shynee (Journal of Health and Allied Sciences NU, 2019)
Background Dysmenorrhea is a common problem which can alter the daily routines of females. Primary dysmenorrhea affects 40 to 90% women. Dysmenorrhea sufferers account for 3 among 4 women as per evidences. Traditional remedies are chosen to get some relief because of their least side effects. These remedies have a favorable effect in reducing dysmenorrhea. Ginger is used since ancient times as various forms of alternative medicine. One of the traditional uses of ginger is for pain relief, including menstrual pain. The aim of this study was to identify the effectiveness of ginger tea in dysmenorrhea.Objectives The objectives of this study are (1) Assess the level of dysmenorrhea among nursing students. (2) Determine the effectiveness of ginger tea on dysmenorrhea among nursing students. (3) Find the association between level of dysmenorrhea before the administration of ginger tea and demographic variables.Methodology A quantitative research approach with quasi-experimental design was considered. The sample comprised of 50 students with moderate and severe menstrual pain as per numerical pain rating scale. The baseline data was collected. Ginger tea was prepared by the researcher and administered 120 mL to the subjects; on the first 2 days of menstruation in the morning and night after breakfast and dinner, respectively. Level of different aspects of pain was assessed before the administration as well as 2 hours after administration of ginger tea using Pain Quality Assessment Scale. Pre- and post-test were taken before as well as 2 hours after administering the drink. A total of four doses are given and ratings were measured eight times. Data was analyzed using descriptive and inferential statistics.Results The present study revealed that the median score of all seven characteristics of pain was higher in the preintervention when compared with postintervention. Mann-Whitney U test showed that there was a significant difference in level of pain between the experimental and control groups (p < 0.05). Wilcoxon signed-rank test showed that there was a significant difference in pain measurements before and after the administration of ginger tea (p < 0.05). These findings indicate that ginger tea was effective in reducing menstrual pain. Chi-square test and likelihood ratio were used to find the association between baseline dysmenorrhea with demographic and clinical variables. It was found that there is no significant association (p > 0.05). The responses given by the experimental and control group was mentioned separately. Ginger tea effects and experience were verbalized by the experimental group alone. This supported the statistical finding that ginger tea is effective in reducing dysmenorrhea.Conclusion Findings revealed that the administration of ginger tea can bring a sudden relief among the subjects with dysmenorrhea. The awareness about alternative therapies must be created among public.
Keywords: ginger tea; effectiveness; dysmenorrhea; nursing students